Prevalence and spatial distribution of intestinal parasitic infections in a rural Amazonian settlement, Acre State, Brazil Prevalência e distribuição espacial de parasitoses intestinais em assentamento agrícola na Amazônia rural, Acre, Brasil - Estéfano Alves de Souza; Mônica da Silva-Nunes; Rosely dos Santos Malafronte; Pascoal Torres Muniz; Marly Augusto Cardoso; Marcelo Urbano Ferreira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
A population-based survey of the prevalence and spatial distribution of intestinal parasitism was carried out in an agricultural settlement in the Amazon Basin of Brazil (Granada, Acre State). More than half (53.4%) of the 429 stool specimens from subjects in all age groups, living in 113 households, had cysts, ova, or larvae of intestinal parasites. The most prevalent parasites were Giardia duodenalis (19.6%) and soil-transmitted helminths (12.7%); 105 (24.5%) subjects were infected with more than one species of parasite. Significant age-related differences in prevalence were only found for G. duodenalis (children < 1 year and adults > 30 years were less affected). Six households (5.3%), situated within a radius of 690m, comprised 48.1% of all subjects harboring soil-transmitted helminths in our study area. Households within this cluster were poorer and more crowded than those outside the cluster. The observed spatial clustering of infections with soil-transmitted helminths provides valuable information for the spatial targeting of sanitary interventions in this area. Estudo de base populacional sobre a prevalência e distribuição de parasitoses intestinais foi realizado em assentamento agrícola na Amazônia Brasileira (Granada, Acre). Mais da metade (53,4%) das 429 amostras analisadas de indivíduos de todas as idades, moradores de 113 domicílios, continha cistos, ovos ou larvas de parasitas intestinais. Os parasitas intestinais de maior prevalência foram Giardia duodenalis (19,6%) e os geo-helmintos (12,7%); 105 (24,5%) indivíduos apresentavam co-infecção por mais de uma espécie de parasita. Houve diferença significativa em relação à idade na prevalência somente de G. duodenalis (crianças < 1 ano e adultos > 30 anos foram menos afetados). Seis domicílios (5,3%), localizados num raio de 690m, concentraram 48,1% de todos os indivíduos infectados por geo-helmintos na área de estudo. Domicílios incluídos nesse agregado (cluster) eram mais pobres e com maior número de habitantes do que os domicílios localizados fora do agregado. A distribuição espacial dos agregados de casos de infecção por geo-helmintos fornece informações valiosas para intervenções sanitárias na comunidade da área de estudo.